2018
DOI: 10.1007/s00330-018-5637-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of recurrent haemoptysis after super-selective bronchial artery coil embolisation: a single-centre retrospective observational study

Abstract: Objectives In recognition of the significant impairment caused by haemoptysis on a patient's quality of life, bronchial artery embolisation has been introduced worldwide as one of the first-line treatment options. Since little evidence is available on the mechanisms of recurrent haemoptysis after super-selective bronchial artery coil embolisation (ssBACE), the purpose of the present study is to evaluate these. Methods We retrospectively evaluated the mechanisms of recurrent haemoptysis using both enhanced comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
(87 reference statements)
4
14
0
Order By: Relevance
“…If sufficient blood flow persists in the perforated bronchial artery at the site of fistula formation, severe haemoptysis akin to a Dieulafoy's lesion in the stomach is likely. We investigated the mechanism of haemoptysis recurrence after ssBACE and reported that haemoptysis recurrence was caused by the recanalization of embolized arteries in 45.2% cases, new haemoptysis‐related vessels in 38.5% cases, bridging collateral (where the distal part of an embolized artery receives blood directly from the proximal part of the embolized artery itself) in 14.7% cases, and conventional collateral (where the distal part of an embolized artery receives blood from a different vessel) in 1.7% cases . These results suggest that 45.2% of embolized arteries had residual flow, although these data are limited to recurrent haemoptysis cases and cannot be directly extrapolated to the present cases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…If sufficient blood flow persists in the perforated bronchial artery at the site of fistula formation, severe haemoptysis akin to a Dieulafoy's lesion in the stomach is likely. We investigated the mechanism of haemoptysis recurrence after ssBACE and reported that haemoptysis recurrence was caused by the recanalization of embolized arteries in 45.2% cases, new haemoptysis‐related vessels in 38.5% cases, bridging collateral (where the distal part of an embolized artery receives blood directly from the proximal part of the embolized artery itself) in 14.7% cases, and conventional collateral (where the distal part of an embolized artery receives blood from a different vessel) in 1.7% cases . These results suggest that 45.2% of embolized arteries had residual flow, although these data are limited to recurrent haemoptysis cases and cannot be directly extrapolated to the present cases.…”
Section: Discussionmentioning
confidence: 94%
“…Various embolic agents are used in BAE, including polyvinyl alcohol, n‐butyl‐2‐cyanoacrylate (NBCA) , gelatine sponges, and metallic coils. BAE using coils (super‐selective bronchial artery coil embolization (ssBACE)) is a relatively new method and is regarded safe and effective . We reported 1‐year haemoptysis‐free rate, 2‐year haemoptysis‐free rate, and major complications as 90.4%, 85.9%, and 1.6%, respectively, in our long‐term follow‐up of 489 ssBACE cases .…”
Section: Introductionmentioning
confidence: 81%
“…Haemoptysis often occurs suddenly and without any prodromal symptoms, such as haemo-sputum [5,10]. Furthermore, patients with haemoptysis experience both acute and chronic decreases in terms of HRQoL [5,11,12]. They typically experience anticipatory anxiety related to their fear of death, which is often strengthened by the sudden onset of haemoptysis and restricted physical activity [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although BAE achieves high technical and clinical success rates with immediate cessation of hemoptysis, a number of studies report the recurrence rate to be as high as 10%-55% (7,8). Recurrent bleeding after BAE may result from incomplete embolization, recanalization of embolized vessels, collateral circulation, or underlying disease progression (2,7,9). Relapsing hemoptysis usually requires repeat embolization, resulting in impaired quality of life and substantial financial cost.…”
Section: Introductionmentioning
confidence: 99%